2022
DOI: 10.1002/biot.202100427
|View full text |Cite
|
Sign up to set email alerts
|

Medium optimization and subsequent fermentative regulation enabled the scaled‐up production of anti‐tuberculosis drug leads ilamycin‐E1/E2

Abstract: Background: Tuberculosis (TB) and its evolving drug resistance have exerted severe threats on the global health, hence it is still essential to develop novel anti-TB antibiotics. Ilamycin-E1/E2 is a pair of cycloheptapeptide enantiomers obtained from a marine Streptomyces atratus SCSIO ZH16-ΔilaR mutant, and has presented significant anti-TB activities as promising drug lead compounds, but their clinical development has been hampered by low fermentation titers. Main methods and major results:By applying the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The inactivation of ilaA and overexpression of ilaB increased the total production of ilamycins to 3.0-and 1.9-fold compared to those in the wild-type S. atratus SCSIO ZH16, respectively (He et al 2020). Medium optimization and subsequent fermentative regulation strategy enabled the scaled-up production of ilamycins E 1 /E 2 to 415.7 ± 29.2 mg/L in S. atratus SCSIO ZH16 ΔilaR in a 300-L bioreactor (Fan et al 2022). However, there are few reports of titer enhancement of ilamycins E 1 /E 2 by fermentative process parameters optimization in wild-type strains and their mutants, especially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inactivation of ilaA and overexpression of ilaB increased the total production of ilamycins to 3.0-and 1.9-fold compared to those in the wild-type S. atratus SCSIO ZH16, respectively (He et al 2020). Medium optimization and subsequent fermentative regulation strategy enabled the scaled-up production of ilamycins E 1 /E 2 to 415.7 ± 29.2 mg/L in S. atratus SCSIO ZH16 ΔilaR in a 300-L bioreactor (Fan et al 2022). However, there are few reports of titer enhancement of ilamycins E 1 /E 2 by fermentative process parameters optimization in wild-type strains and their mutants, especially.…”
Section: Introductionmentioning
confidence: 99%
“…Medium optimization and subsequent fermentative regulation strategy enabled the scaled-up production of ilamycins E 1 /E 2 to 415.7 ± 29.2 mg/L in S . atratus SCSIO ZH16 Δ ilaR in a 300-L bioreactor (Fan et al 2022 ). However, there are few reports of titer enhancement of ilamycins E 1 /E 2 by fermentative process parameters optimization in wild-type strains and their mutants, especially.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the specific impact of any kind of organic nitrogen source on the growth of bacteria and synthesis of natural products, one bacterium or its genetic mutant has unique preference for organic nitrogen sources. Previous studies indicated the significant effect of the selection of organic nitrogen source on the yield of ilamycins in S. atratus SCSIO ZH16 Δ ilaR [ 7 , 24 ]. In view of this, this study started with the systematic screening of composite nitrogen sources on S .…”
Section: Resultsmentioning
confidence: 99%
“…atratus SCSIO ZH16, nonribosomal peptides ilamycins, especially ilamycin E, show brilliant anti-tuberculosis properties [ 9 ], and require yield improvement for the realization of industrial production or process. By Plackett–Burman design model, single factor optimization, pH coordinated feeding and continuous pulse feeding, [ 7 ] achieved 415.7 ± 29.2 mg/L ilamycin E yield in a 300 L bioreactor. Our previous research also improved the production of ilamycin E from 13.51 to 762.50 mg/L in a 5 L bioreactor, and found the crucial role of nitrogen source on cellular growth of ZH16-Δ ilaR and the production of ilamycins [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As biosynthesis has become increasingly popular, traditional methods usually have the problems of difficult process, complex by‐products, low yield, and shortage of supply. In response, a number of efforts have been made, such as media optimization, 131 metabolic pathway modification, 132 and traditional breeding methods 133 . However, these methods and techniques are still limited and inefficient in obtaining the desired phenotype.…”
Section: Application Of Artp In the Field Of Mutagenesismentioning
confidence: 99%